Papua: Sejarah Integrasi yang Diingat dan Ingatan Kolektif - Ester Yambeyapdi (Indonesian Historical Studies, 2018)
National integration issue is inherently dynamic and tends to follow the social changes. It is because the problem cannot be taken for granted. This situation is also very dependent on the way and the tendency of a political regime to understand and treat the aspirations of the people in a particular space and time. Based on this matter, this paper analyzes the government's efforts to create national integration in Papua (social, economic, political conditions) and how Papuans interpret the post-New York 1962 integration process, the 1969 Act until the first four years after the Act. Based on the structuralist approach and the theory of political integration, it was found that since Papuans began to adapt to Indonesians, they experienced a new atmosphere, such as the Indonesian government system which is different from the Dutch colonial government. The social, political, and economic life must undergo a period of quarantine which is primarily determined by the interests of the authorities. This situation encourages groups that have certain interests in society. There are Indonesian pro-integration groups, and there are anti-integration groups that manifest themselves in the Free Papua Organization (OPM), and some other social protest movements to date.